Health status of elderly: a comparative study among urban and rural dwellers - Zare, V. R.; Kokiwar, Prashant; Ramesh, B. (International Journal Of Community Medicine And Public Health, 2018)
Background: Due to advancement in the medical science, the life expectancy is showing an increase in every census. Hence there is also growing demand to have good quality of life among the elderly. The objective of the study was to assess and compare the health status of elderly in urban areas of Shapur and rural areas of Gummadidala. Methods: A Community based cross sectional study was carried out in rural areas located at Gummadidala, Nallavelli, Anantharam and in urban areas located at Shapur, Kalavathinagar, Subashnagar among geriatric aged people above 60 years. Study was conducted over a period of eight months from August 2017 to March 2018. Results: Overall almost all diseases were more common in rural elders compared to the urban elders except gynecological diseases. Among these hypertension, ear diseases, skin diseases, musculoskeletal disorders, psychological disorders, cancer and neurological diseases were significantly more common in rural elders than urban elders (p<0.05). Only gynecological diseases were significantly more common in urban women and this may be due to more percentage of hysterectomies among rural females. Conclusions: Elderly people in the rural areas are more prone to suffer from diseases as compared to their urban counterparts.